When Are ?Female? Occupations Paying More? - Štepán Jurajda; Heike Harmgart (Institute for the Study of Labor (IZA), 2004)
We compare the importance of occupational gender segregation for the gender wage gap in East and West Germany in 1995 using a sample of social-security wage records of full-time workers. East Germany, which features a somewhat higher degree of occupational segregation, has a gender wage gap on the order of one fifth of the West German gap. Segregation is not related to the West German wage gap, but in East Germany, wages of both men and women are higher in predominantly female occupations. East German female employees apparently have better observable and unobservable characteristics than their male colleagues. These findings are in contrast to a large U.S. literature, but are consistent with the imposition of high wage levels in East Germany at the outset of reforms and the selection of only high-skill women into employment. Finally, conditioning on unobservable labor quality differences using the longitudinal dimension of the data, there is a negligible impact of segregation in both parts of Germany.
Keywords: J71; J21; J16; 330; occupational segregation; gender wage gap; Frauenarbeitslohn; Lohndifferenzierung; Arbeitsmarktsegmentierung; Geschlecht; Schätzung; Neue Bundesländer